The invention of prehistory : empire, violence, and our obsession with human origins - Geroulanos, Stefanos, 1979- (Liveright Publishing Corporation, a division of W.W. Norton & Company, 2024)
"In this remarkable and enlivening study, Stefanos Geroulanos traces the development of our modern fascination with humanity's deep past, and lays out that fascination's deadly costs." --Amia Srinivasan, author of The Right to Sex: Feminism in the Twenty-First Century An eminent historian tells the story of how we came to obsess over the origins of humanity--and how, for three centuries, ideas of prehistory have been used to justify devastating violence against others.